Isolation and Genetic Characterization of Methicillin–Resistant Staphylococcus aureus (MRSA) from Animal Products in Khartoum State, Sudan - Khalil, Alaa; Gamar, Alaa; Elmahy, Elshima; Abdalla, Enass M.; Fadul, Mashaer; Mukhtar, Mohamed E.; Elsanousi, Reem M. A.; Musa, Mohamed T.; Ahmed, Sharfi A. O.; El Sanousi, Sulieman M.; Eltom, Kamal H. (Journal of Veterinary Medicine and Animal Production, 2022)
The aim of this study was to investigate the presence of methicillin-resistant Staphylococcus aureus (MRSA) in animal products to contribute in establishing epidemiological data on antimicrobial resistance in the Sudan. Samples (N = 616) of animal products (milk, cheese, chicken and retail meat) were collected from different sources in Khartoum State and subjected to bacteriological and molecular biology techniques for isolation and characterization of S. aureus. S. aureus was isolated from 62 (10.1%) of the samples with frequencies of 32.7%, 23.3%, 21.5% 7.2% and 4.75% from cheese, chicken meat, retail meat, camel milk and cattle milk, respectively. Methicillin resistance was detected phenotypically among all (100%) cattle milk, 78.6% of retail meat, 71.4% of chicken meat, 50% of camel milk and 23.5% of cheese S. aureus isolates. The methicillin resistance gene (mecA) was detected in 3 isolates with one being positive for mecA analogue (mecC) as well. mecA gene detected in these isolates belonged to none of S. aureus SCCmec (staphylococcal cassette chromosome mec) known types. Panton-Valentine Leuckocidin (PVL), haemolysin (hlg) and toxic shock syndrome toxin (tsst) genes were detected as 12.9%, 9.7% and 0.0%, respectively, in all S. aureus isolates. High prevalence of methicillin resistance among S. aureus isolates from animal products, especially from cattle milk indicates widespread of antimicrobial resistance and necessitates adoption of good animal production hygiene practices. The genes responsible for methicillin resistance among phenotypically MRSA but mecA/mecC-negative strains are yet to be identified.